From fleece to screens: Revolutionizing sheep and goat marketing in the digital age - Gashaw, Tsehay (CGIAR System Organization, 2023)
Recognizing the transformative potential of digital marketing, a partnership was formed between the CGIAR Initiative on Sustainable Animal Productivity or SAPLING, the Accelerating the Impact of CGIAR Climate Research for Africa (AICCRA) project and YAZERBER, a private sector entity dedicated to the production, branding, marketing, and distribution of livestock farm products and services. YAZERBER played a crucial role in developing digital marketing.